2013
DOI: 10.1159/000349988
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Care of Patients with Chronic Lymphoedema in Germany

Abstract: Background: The management of lymphoedema is complex and should be based on guidelines. To date, no data assessing quality of care in lymphoedema in Germany are available. Objective: We aimed at evaluating the quality of care of lymphoedema in the metropolitan area of Hamburg using guideline-based indicators. Methods: Cross-sectional, community-based study including patients with lymphoedema. Assessment included a structured interview, clinical examination and patient-reported outcomes. Quality indicators deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…In Germany, only 64.8% of patients were found to be satisfied with lymphoedema treatment, although 86.4% of the patients underwent compression therapy and 85.6% received lymphatic drainage (Herberger et al, 2013). Based on these results, it is necessary to develop new treatments in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In Germany, only 64.8% of patients were found to be satisfied with lymphoedema treatment, although 86.4% of the patients underwent compression therapy and 85.6% received lymphatic drainage (Herberger et al, 2013). Based on these results, it is necessary to develop new treatments in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In this article we have published data in relation to the validation of the FLQA‐LS. However, other data obtained from questionnaires and personal interviews with the patients have been analysed and have been or will be published in separate papers …”
Section: Discussionmentioning
confidence: 99%
“…Community‐based studies have shown a high patient need for treatment and health care . However, in Germany, like in many countries, patients with chronic lymphoedema receive only a moderate level of health care . In particular, early diagnosis and treatment are frequently missed …”
mentioning
confidence: 99%
“…Recent data support early treatment of lymphedema by demonstrating a positive effect of efficient lymphedema treatment on quality of life . Specific lymph therapy has been shown to increase the quality of care in the community …”
mentioning
confidence: 96%
“…Furthermore, complications such as erysipelas and chronic ulceration may arise . Health care studies in Germany have demonstrated that the quality of care is largely inadequate …”
mentioning
confidence: 99%